Corrosion Inhibition Effect of Carbon Steel in Sea Water by L-Arginine-Zn2+ System - S. Gowri; J. Sathiyabama; S. Rajendran (International Journal of Chemical Engineering)
The inhibition efficiency of L-Arginine-Zn2+ system in controlling corrosion of carbon steel in sea water has been evaluated by the weight-loss method. The formulation consisting of 250 ppm of L-Arginine and 25 ppm of Zn2+ has 91% IE. A synergistic effect exists between L-Arginine and Zn2+. Polarization study reveals that the L-Arginine-Zn2+ system functions as an anodic inhibitor and the formulation controls the anodic reaction predominantly. AC impedance spectra reveal that protective film is formed on the metal surface. Cyclic voltammetry study reveals that the protective film is more compact and stable even in a 3.5% NaCl environment. The nature of the protective film on a metal surface has been analyzed by FTIR, SEM, and AFM analysis.